Behavior based estimation of dependability for autonomous mobile systems using particle filter - Rüdiger, Jan; Wagner, Achim; Badreddin, Essameddin (17th IFAC world congress 2008 ; Vol. 3, 2009)
Abstract: The dependability of a system is particularly important when dealing with autonomous or semi-autonomous systems. With an increasing degree of autonomy and safety requirements, the requirements for dependability increase. Hence, being able to measure and compare the dependability of a system is more and more inevitable. Since autonomous mobile systems are usually described by their behavior it is straightforward to also define the dependability of such a system in a behavioral context. Thus, in this paper, the approach of a behavioral based definition of dependability is used together with a Particle Filter to predict the dependability of an autonomous mobile system at runtime.
Gesehen am 23.04.2019